Determinants of the Uptake of Intermittent Preventive Treatment of Malaria in Pregnancy with Sulphadoxine Pyrimethamine in Sabatia Sub County, Western Kenya - Mutanyi, Joshua A.; Onguru, Daniel O.; Ogolla, Sidney O.; Adipo, Lawrence B. (BMC, 2021)
Annually, 125.2 million pregnant women worldwide risk contracting malaria, including 30.3 million and 1.5 million in Sub-Saharan Africa and Kenya respectively. At least three doses of sulphadoxine pyrimethamine for intermittent preventive treatment of malaria in pregnancy (IPTp-SP) is recommended for optimal benefit. Kenya recorded low IPTp-SP optimal uptake in 2015. This study investigated the prevalence of and factors influencing IPTp-SP optimal uptake in Sabatia Sub County, Western Kenya. A cross-sectional study was conducted in Sabatia Sub County from April to October 2020. Using a validated semi-structured questionnaire, data were obtained from 372 randomly sampled post-delivery women aged 15–49 years with live birth within one year preceding the study. Women on cotrimoxazole prophylaxis during preg- nancy were excluded. Pearson Chi-square and Fisher’s Exact test were measures of association used. Binary logistic regression analysed predictors of optimal IPTp-SP uptake. Results: Optimal IPTp-SP uptake was 79.6%, 95% CI 75.5%–83.7%. Predictors of IPTp-SP optimization were gestational age at first antenatal care (ANC) visit (P = 0.04), frequency of ANC visits (P < 0.001), maternal knowledge of IPTp-SP benefits (P < 0.001), maternal knowledge of optimal sulphadoxine pyrimethamine (SP) dose (P = 0.03) and SP administration at ANC clinic (P = 0.03). Late ANC initiators were less likely to receive optimal IPTp-SP (aOR = 0.4, 95% CI 0.2–0.9). Odds of optimizing IPTp-SP increased among women with ≥ 4 ANC visits (aOR = 16.7, 95% CI 7.9–35.3), good knowledge of IPTp-SP benefits (aOR = 2.4, 95% CI 1.3–4.5) and good knowledge of optimal SP dose (aOR = 1.9, 95% CI 1.1–3.4). Women who never missed being administered SP were highly likely to receive optimal IPTp-SP (aOR = 2.9,95% CI 1.1–7.2). This study has found high IPTp-SP optimal uptake in the study area. Efforts should be directed towards early and more frequent ANC visits. Intensive and targeted health education is required. It’s fundamental to adequately stock and consistently administers SP. Future studies considering larger samples and health workers’ perspectives of the health system delivery factors are recommended.
Keywords: Malaria; Pregnancy; Intermittent Preventive Treatment; Sulphadoxine Pyrimethamine; Sabatia